Eurogel '91 : progress in research and development of processes and products from sols and gels : proceedings of the Second European Conference on Sol-Gel Technology, Saarbrucken, Germany, June 2-5, 1991 - Vilminot, S.; Nass, R.; Schmidt, H. (European Materials Research Society monographs, 1992)
Eurogel '91 is the second conference to report on the developments in research and technology of European laboratories and industry. The volume focuses on the scientific and technological progress in the field, as well as providing a global overview of the latest developments. The fifty presented papers report on many new themes and research groups. Expansion in the utilization of the sol-gel process for new products and processes is developing steadily. Application requires an interdisciplinary effort beginning with application orientated fundamental research and ending up with engineering and technology. This interdisciplinary contact can be enhanced by closer cooperation between research and industry. In particular, potential users of innovative materials should become more aware of the possibilities connected with sol-gel technologies. At present the sol-gel process is considered as one of the most important technologies for developing innovative glasses, ceramics and composites. The contributions in this volume will be of interest to all those who are involved in the development potential of industrial and market needs.